2016
DOI: 10.1017/ice.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Surveillance Events Detected by National Healthcare Safety Network Pneumonia and Lower Respiratory Infection Definitions—Pennsylvania, 2011–2012

Abstract: Objective To determine the clinical diagnoses associated with National Healthcare Safety Network (NHSN) pneumonia (PNEU) or lower respiratory infection (LRI) surveillance events. Design Retrospective chart review. Setting Eight acute care hospitals in Pennsylvania. Patients All patients hospitalized during 2011–2012. Methods Medical records were reviewed from a random sample of patients reported to NHSN to have PNEU or LRI, excluding adults with ventilator-associated PNEU. Documented clinical diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…NV-HAP has been associated with increased mortality 38,39 ; the in-house mortality rate for NV-HAP cases in our study was 15.8%, which was similar to that reported by Micek et al (15.5%), 8 but less than See et al (30.9%). 9 In addition, hospital stays with ICU involvement are 2.5 times costlier than hospital stays with no ICU stay. 40 Therefore, patients in the ICU with NV-HAP contribute to increased LOS, mortality, and cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NV-HAP has been associated with increased mortality 38,39 ; the in-house mortality rate for NV-HAP cases in our study was 15.8%, which was similar to that reported by Micek et al (15.5%), 8 but less than See et al (30.9%). 9 In addition, hospital stays with ICU involvement are 2.5 times costlier than hospital stays with no ICU stay. 40 Therefore, patients in the ICU with NV-HAP contribute to increased LOS, mortality, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a further study of a convenience sample of 8 hospitals in Pennsylvania, most health care-associated pneumonia cases were reported outside of a critical care setting (74.1%), the mortality rate of pneumonia patients reached 30.9%, and a quarter of health care-associated pneumonia cases were attributed to aspiration, a cause which could be minimized through nursing activities targeted at aspiration prevention. 9 Our previous report from the Hospital-Acquired Pneumonia Prevention Initiative (HAPPI-1) highlighted a significant number of unreported NV-HAP cases (1.2-8.9 per 1,000 hospital days) in a convenience sample of 3 U.S. hospitals. 3 After implementation of an evidence-based, oral care protocol aimed at NV-HAP prevention for all acute care patients in 1 hospital, the rate of NV-HAP per 100 patient discharges decreased by 38.8% from 0.5 to 0.3.…”
mentioning
confidence: 99%
“…1,2,3 Crude mortality rates for patients with nonventilator hospital-acquired pneumonia (NV-HAP) range between 15% and 30%, which are similar to or higher than the rates associated with ventilator-associated pneumonia. 3,4,5,6,7,8,9 Most hospitals, however, do not have formal surveillance or prevention programs for NV-HAP. 3,10,11,12…”
Section: Introductionmentioning
confidence: 99%
“…6 More than one-quarter of HAP cases is attributable to aspiration, which is considered a modifiable risk factor. 7 The prevalence and etiology of hospital-acquired aspiration pneumonia (HAAP) in hospitalized patients with cancer is not well described or understood.…”
mentioning
confidence: 99%
“…13,14 A recent epidemiological study examining clinical correlates of HAP reported that 48.2% of patients with HAP also had malignancy, and another 29.6% were immunocompromised. 7 Thus, a number of factors may potentially contribute to the development of HAAP.…”
mentioning
confidence: 99%